The Role of Business Strategy Using Information Technology on Branch Offices in Indonesian Sharia Banking - Asep Ghofir Ali; Ucu Supriatna (Asia Pacific Journal of Management and Education (APJME), 2025)
The development of information technology (IT) in the banking sector has transformed service delivery, including in Sharia banking in Indonesia. Digital banking has become a crucial strategy to meet customer needs and enhance competitiveness, especially considering the limited number of Sharia bank office networks compared to conventional banks. This study aims to examine the influence of IT and office networks on the implementation of IT-based business strategies in Indonesian Sharia banking. Using a descriptive-verificative approach, the research applies an explanatory survey method by distributing questionnaires to gather data from selected respondents. The results show that IT has a significant positive effect on the implementation of IT-based business strategies (coefficient = 0.628; T = 2.766; p = 0.006), while the office network does not show a significant direct influence (coefficient = 0.269; T = 1.443; p = 0.150). However, when combined, IT and office networks have a significant simultaneous effect on technology-based business strategies. This implies that although physical office networks remain important, digital infrastructure plays a more dominant role in driving strategic business initiatives in Sharia banking. Strengthening IT systems should be prioritized to enhance service delivery and achieve long-term business goals.